Jus ad pacem in bello? Afghanistan, stability operations and the international laws relating to armed conflict - Turns, David (U.S. Naval War College, 2009)
One of the more notorious quotations widely attributed to George W. Bush, when he was campaigning for the presidency of the United States in 2000, was something lathe effect that "[w]e don't do nation-building." As with many attributed quotations. the actual remark he made was less curt and slightly more nuanced.